Kinematic Analysis of Postural Stability During Ballet Turns (pirouettes) in Experienced and Novice Dancers - Lin, Chai-Wei; Su, Fong-Chin; Lin, Cheng-Feng (Frontiers in Bioengineering and Biotechnology, 2019)
Turning is an important but difficult movement often performed in ballet choreography. Understanding the postural sway during ballet turns is beneficial to both dancers and dance teachers alike. Accordingly, this study evaluated the postural sway angle during ballet turns in female novice and experienced ballet dancers by means of the inclination angle determined from the center of mass (COM) and center of pressure (COP). Thirteen experienced dancers and 13 novice dancers performed ballet turns (pirouettes). The COM-COP inclination angle was measured during the preparatory, double-leg support, and single-leg support phases of the turn. The novice dancers exhibited significantly greater ranges of the COM-COP inclination angle in the anterior-posterior (AP) and medial-lateral (ML) directions during the preparatory (AP direction, p < 0.001; ML direction p=0.035), double-leg support (AP direction p < 0.038; ML direction p=0.011), and ending phases (AP direction p < 0.001; ML direction p=0.024). Moreover, during the preparatory phase, the novice dancers failed to adjust their posture in a timely manner, and therefore showed overshooting errors. Finally, during the ending phase, the novice dancers showed a greater standard deviation of the COM-COP inclination angles and performed continual postural adjustments, leading to a less smooth movement than the experienced dancers. In conclusion, the novice dancers were suggested to focus on the COM-COP adjustment during both preparatory and ending phases.